Implications of the use of bisphosphonates in dental treatment – experience of the service of oral and maxillofacial surgery, Erasto Gaertner Hospital, Curitiba, Brazil - Regiane Benez Bixofis; Laurindo Moacir Sassi; Cleverson Patussi; William Phillip Pereira da Silva; Roberta Targa Stramandinoli Zanicotti; Juliana Lucena Schussel (Revista Sul-Brasileira de Odontologia, 2014)
Bisphosphonates (BP) are effective drugs in the prevention and treatment of various bone pathologies, acting in the regulation of osteoclast function through different mechanisms. Despite the success in the treatment of various diseases, these drugs have the ability to induce an avascular necrosis of bone tissue, especially in the maxilla and mandible. Objective: Due the significant increase number of cases of patients with oral complications associated with BP therapy in the Department of Oral and Maxillofacial Surgery of the Erasto Gaertner Hospital, the study aimed to report our experience in the care of these patients. Material and methods: Patients submitted to BP therapy were enrolled prospectively between the years of 2011 and 2012. Clinical examination was performed in all patients to evaluate dental health as well oral mucosa. All patients are under follow-up in our service. Results: 26 patients who used BP were attended in the ambulatory. Twenty-three patients used BP for oncological indication and three for osteoporosis. Most of patients were women (66%) with average age of 56 years old. The most frequent medication used was Pamidronate (54%), followed by Zoledronic acid (30%) and Alendronate (15%). Ten patients showed bone exposition, most of then in the mandible (80%), with an average time of one year of exposure. Conclusion: Dentists should advise their patients about the use of BP and the implications for oral health and treatments. These patients must have periodic consultations for evaluation and early detection of osteonecrosis associated to BP for adequate treatment.